Appointment of N. I. Strakhov as the chief bailiff of the kalmyk people (based on the materials of russian legislation of 1801–1802) - E. A. Komandzhaev; A. N. Komandzhaev (Nomadic Civilization: Historical Research)
The relevance of this study is explained by its lack of knowledge The relevance of this study is explained by the lack of knowledge on the stated problems: there are no special works on the topic, in most works the problem is considered fragmentarily, although all researchers who studied the history of Kalmykia at the beginning of the 19th century always mentioned the name of N.I. Strakhov as an administrative figure or his work. Assources the authors use the texts of laws approved by Alexander I in October 1801-May 1802, published in 26–27 volumes of the Complete Collection of Laws of the Russian Empire. The authors identified the most important document from the State Archive of the Astrakhan Region (“Command of Alexander I to the Astrakhan Civil Governor Povalishin”), which is associated with the appointment of N. Strakhov. The purpose of this article is to study the process of appointing N.I. Strakhov as the Chief Bailiff of the Kalmyk people based on materials from Russian legislation. The enormous significance of this issue at the beginning of the 19th century was due to the changed geopolitical situation in the south of Russia after the Kalmyk exodus of 1771. Previously, it was the Kalmyk Khanate with its army that provided guarantees for the security of the borders of the Russian Empire. But even after 1771, the Russian administration continued to place high hopes on the Kalmyks. Kalmyks are a Buddhist people with their own worldview, with an established nomadic way of life and centuries-old experience of statehood and legislative tradition, with an organized military structure and weapons, with established long-standing social groups, an ancient written culture and its institutions. These features of the Kalmyks were certainly taken into account by the Russian authorities in their policies at the beginning of the 19th century. Such close attention of Emperor Alexander I to the appointment of N.I. Strakhov as the Chief Bailiff of the Kalmyk people was a recognition of the significant role of the Kalmyks in the region and its civilizational and cultural isolation.